Smart Healthy Age-Friendly Environments (SHAFE) Bridging Innovation to Health Promotion and Health Service Provision - Vincenzo De Luca; Hannah Marston; Leonardo Angelini; Nadia Militeva; Andrzej Klimczuk; Carlo Fabian; Patrizia Papitto; Joana Bernardo; Filipa Ventura; Rosa Silva; Erminia Attaianese; Nilufer Korkmaz; et al. (Intergenerational Relations: Contemporary Theories, Studies and Policies, 2024)
A number of experiences have demonstrated how digital solutions are effective in improving quality of life (QoL) and health outcomes for older adults. Smart Health Age-Friendly Environments (SHAFE) is a new concept introduced in Europe since 2017 that combines the concept of Age-Friendly Environments with Information Technologies, supported by health and community care to improve the health and disease management of older adults and during the life-course. This chapter aims to provide an initial overview of the experiences available not only in Europe, based on the research work of the participants of the International Interdisciplinary Network on Health and Well-being in an Age-Friendly Digital World (NET4Age-Friendly), which could be of interest to preventive, health and social authorities. The chapter reports good practices, pain points, and bottlenecks that may require a collaborative, interdisciplinary research approach to facilitate the transformations towards smart, sustainable, health and age-friendly cities and communities.
Keywords: R50; J14; 330; age-friendly cities and communities; digital integrated care; integrated health services; people-centred health services; smart built environments